University Calculus: Early Transcendentals (3rd Edition)

Published by Pearson
ISBN 10: 0321999584
ISBN 13: 978-0-32199-958-0

Chapter 11 - Section 11.2 - Vectors - Exercises - Page 609: 42



Work Step by Step

Since, we have $u=u_1+u_2$ or, $i-2j=a(2i+3j)+b(i+j)$ or, $2a+b=1; 3a+b=-2$ After solving the above two equations, we have $a=-3$ From equation $2a+b=-1 \implies 2(-3)+b=1$ or, $b=7$ Hence, $u=u_1+u_2=-3(2i+3j)+7(i+j)=(-6i-9j)+(7i+7j)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.